P118 Podoplanin regulates the migration of mesenchymal stromal cells and their interaction with platelets. (March 2019) - Ward, L; Sheriff, L; Marshall, J; Manning, J; Nash, G; Mcgettrick, HM
Abstract : Career situation of first and presenting author: Young investigator. Introduction: Within the rheumatoid joint, mesenchymal stromal cells (MSC) up-regulate podoplanin with unknown consequences for disease pathogenesis. The function of podoplanin has been linked to enhanced migratory potential and interactions with platelets. However, it is unclear how these two cell types interact with one another, given that MSC and platelets are usually located in in different anatomical compartments (tissue vs blood respectively) separated by the blood vascular endothelial cells (EC). Objectives: Here, we examined the functional consequences of podoplanin expression on the migratory potential of MSC and their interactions with circulating platelets. Methods: Human MSC were isolated from healthy controls Comparisons were made between podoplanin positive and negative MSC. MSC migration across 8 um pore filters following treatment with anti-siRNA podoplanin or Rho GTPases inhibitors was assessed. MSC-platelet interactions were assessed by culturing MSC on the basal surface of 3 um pore filters and perfusing fluorescently labelled platelets in whole blood over the apical surface. In some cases, the apical surface of the filter was pre-coated with EC, forming an EC-MSC co-culture, prior to platelet perfusion. Results: Expression of podoplanin significantly enhanced the migration of MSC compared to MSC lacking podoplanin. Rac-1 inhibition altered the membrane localisation of podoplanin and in turn significantly reduced MSC migration. Blocking Rac-1 activity had no effect on the migration of MSC lacking podoplanin, indicating it was responsible for regulation of migration through podoplanin. When podoplanin-expressing MSC were seeded on the basal surface of a porous filter, they were able to capture platelets perfused over the uncoated apical surface and induce platelet aggregation. Similar microthrombi were observed when EC were co-cultured on the apical surface. Confocal imaging shows podoplanin-expressing MSC extending processes into the EC layer, which could interact with circulating platelets. In both models, platelet aggregation induced by podoplanin-expressing MSC was inhibited by recombinant soluble CLEC-2. Conclusions: Podoplanin enhances the migratory capacity of tissue-resident MSC enabling them to move more rapidly within the rheumatoid joint. Moreover, podoplanin allows MSC to interact with both circulating and tissue platelets to elicit either protective or pathogenic responses. Acknowledgements: This work was funded by an Versus Arthritis Career Development Fellowship, a MRC-funded PhD studentship and BHF Grant. Disclosure of Interest: None declared.